2017
DOI: 10.1101/124388
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Large scale and significant expression from pseudogenes in Sodalis glossinidius - a facultative bacterial endosymbiont

Abstract: The majority of bacterial genomes have high coding efficiencies, but there are some genomes of intracellular bacteria that have low gene density. The genome of the endosymbiont Sodalis glossinidius contains almost 50% pseudogenes containing mutations that putatively silence them at the genomic level. We have applied multiple ‘omic strategies, combining: Illumina and Pacific Biosciences Single-Molecule Real Time DNA-sequencing and annotation; stranded RNA-sequencing; and proteome analysis to better understand t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 78 publications
3
4
0
Order By: Relevance
“…Likewise, amino acid transport appears to occur frequently between the gut microbiome and honeybees (71). Sodalis glossinidius was enriched in functions related to transposition, consistent with a recent study that evaluated the genomic landscape of Sodalis glossonidius and showed that a large part of it encoded for transposition-related pseudogenes (72). Importantly, Sodalis praecaptivus is considered to be the only currently known free-living form of Sodalis bacteria (73), while…”
Section: Discussionsupporting
confidence: 80%
“…Likewise, amino acid transport appears to occur frequently between the gut microbiome and honeybees (71). Sodalis glossinidius was enriched in functions related to transposition, consistent with a recent study that evaluated the genomic landscape of Sodalis glossonidius and showed that a large part of it encoded for transposition-related pseudogenes (72). Importantly, Sodalis praecaptivus is considered to be the only currently known free-living form of Sodalis bacteria (73), while…”
Section: Discussionsupporting
confidence: 80%
“…It has been noted previously that argC is pseudogenized (29), but the new annotation indicates that this may not be the case. ArgC is also detected by proteomics, suggesting that this gene is indeed likely functional (47).…”
Section: Resultsmentioning
confidence: 99%
“…This is particularly relevant in symbiotic bacteria where the functionality of broken or fragmented genes is not certain. Indeed, a recent report implies that some S. glossinidius genes thought to be pseudogenized are in fact under transcriptional control (47).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the high synteny and high expression levels of most PGs imply that they have not likely been gained through HGT, but are the result of degradation of native genes. Indeed, large scale pseudogenization that is due to such degradation appears to be characteristic to intracellular bacteria, as many of their genes become inactivated during the transition from an independent lifestyle to the more stable environment of their host [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%